PENGEMBANGAN MEDIA INTERAKTIF MAGICBOOK BERBASIS AUGMENTED REALITY ANDROID PADA MATA DIKLAT MENERAPKAN FUNGSI PERIFERAL DAN INSTALASI PC - Reni Kurnia; Asrul Huda; Nurindah Dwiyani (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The problem in this final project is an internal problem of the school is the availability of school facilities and infrastructures are affected to the students’ knowledge of X TKJ in identifying the type of devices peripheral and its functions. Other causes are the teaching methods and learning medias which used not various, it makes learning become less enjoyable. To overcome these problems, then designed a technology-based Learning Media MagicBook Augmented Reality using Android mobile devices. Besides being able to combine the virtual objects with the reality environtment, Augmented Reality technology enables users to perform three-dimensional direct interaction thus better able to give the impression for students. Magicbook Learning Media is designed like a regular book, but in inside the Magicbook is inserted a marker as a link between the real world and the virtual objects, then added with animation and video tutorials use the application. This media is created using Vuforia Library, Unity Free and Mono Development, Autodesk 3D Studio Max as animation maker software. This media is designed to assist students in understanding the concept of training courses of Apply the Function of Instalation PC and Peripherals and assist teachers in explaining the material. Keywords         :Interactive Media, Magicbook, Augmented Reality, Marker.